2019
DOI: 10.1002/chem.201903854
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of a Trithioorthoformate‐Capped Cyclophane and Its Endohedral Inclusion of a Methine Group

Abstract: An unusual trithioorthoformate‐capped cyclophane cage was assembled via antimony‐activated iodine oxidation of thiols as confirmed by 1H‐NMR spectroscopy and X‐ray crystallography. The disulfide bridges can undergo desulfurization with hexamethylphosphorous triamide (HMPT) at ambient temperature to capture a trithioether cyclophane cage capped by the trithioorthoformate. In both cages a methine proton points directly into the small cavity. This unexpected structure is hypothesized to have formed as a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
4
2
Order By: Relevance
“…In stark contrast to previously reported orthoformate 1.1.1 ‐cryptands and trithioformate cages, the ring is sufficiently large to enable this isomerization and o ‐(H out ) 2 ‐2.2.2 is thermodynamically favored over o ‐(H in ) 2 ‐2.2.2 (2 : 1 molar ratio in CD 3 CN, Figure c, II ). In less polar solvent chloroform we observed an equimolar mixture of o ‐(H out ) 2 ‐2.2.2 and o ‐(H in ) 2 ‐2.2.2 (1 : 1 molar ratio in CDCl 3 , see Supporting Information), which can be rationalized by a less effective completion of the solvent with the intramolecular hydrogen bonds.…”
Section: Methodscontrasting
confidence: 69%
See 1 more Smart Citation
“…In stark contrast to previously reported orthoformate 1.1.1 ‐cryptands and trithioformate cages, the ring is sufficiently large to enable this isomerization and o ‐(H out ) 2 ‐2.2.2 is thermodynamically favored over o ‐(H in ) 2 ‐2.2.2 (2 : 1 molar ratio in CD 3 CN, Figure c, II ). In less polar solvent chloroform we observed an equimolar mixture of o ‐(H out ) 2 ‐2.2.2 and o ‐(H in ) 2 ‐2.2.2 (1 : 1 molar ratio in CDCl 3 , see Supporting Information), which can be rationalized by a less effective completion of the solvent with the intramolecular hydrogen bonds.…”
Section: Methodscontrasting
confidence: 69%
“…In stark contrast to previously reported orthoformate 1.1.1cryptands and trithioformate cages, [7,12] the ring is sufficiently large to enable this isomerization [2a,3] Because under these conditions both homeomorphic and DCvC inversion are possible, we believe that this mixture corresponds to the global thermodynamic equilibrium of the network (molar ratio out,out-, in,in-, and in,out-cryptand ca. 2 : 1 : 2 in CD 3 CN).…”
contrasting
confidence: 70%
“…13 The tripodal nature of orthoesters makes them uniquely suited for the self-assembly of cage-type architectures. 14,15 Also, orthoester exchange gives rise to a remarkable level of molecular diversity, because by mixing one orthoester with one alcohol, an equilibrium mixture consisting of four different orthoesters is obtained (Scheme 1A). In contrast, dithioacetal exchange produces fewer products (Scheme 1B) and is more suited to the preparation of cyclic hosts.…”
Section: Published As Part Of the Cluster Metathesis Beyond Olefinsmentioning
confidence: 99%
“…Recently, we have shown that this strategy can be applied to the formation of cyclophanes from benzylic di‐ and trithiol precursors by manipulating dynamic disulfide exchange with the inclusion of a pnictogen (Pn) directing agent coupled with a mild oxidant [17–19] . Our approach complements related disulfide exchange and self‐assembly methods that proceed via aerobic oxidation and/or macrocyclization pathways [20] , and it enables quick (as fast as 5 minutes) and quantitative formation of discrete disulfide‐bridged macrocycles and cages over extended oligomers using a variety of simple di‐ and/or trithiols [17,21,22] …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Recently, we have shown that this strategy can be applied to the formation of cyclophanes from benzylic di-and trithiol precursors by manipulating dynamic disulfide exchange with the inclusion of a pnictogen (Pn) directing agent coupled with a mild oxidant. [17][18][19] Our approach complements related disulfide exchange and self-assembly methods that proceed via aerobic oxidation and/or macrocyclization pathways [20] , and it enables quick (as fast as 5 minutes) and quantitative formation of discrete disulfide-bridged macrocycles and cages over extended oligomers using a variety of simple di-and/or trithiols. [17,21,22] Moreover, using design of experiments (DOE), [22] we have shown we can easily bias the self-assembly reaction mixture to optimize specific multimeric products [23] and, using self-sorting methods, readily form asymmetric disulfide macrocycles [24] .…”
Section: Introductionmentioning
confidence: 99%